Effects of annealing temperature on magnesium deficient in MgB2 superconductor - M. Faisal, M. A.; Halim, S. A.; Chen, S. K.; Abd-Shukor, R.; Awang Kechik, M. M.; Baqiah, H. (Malaysian Solid State Science and Technology Society, 2016)
The Mg-deficient Mg0.8B2 superconductors were prepared using the solid-state reaction method at different annealing temperature between 650 °C and 800 °C. The x-ray diffraction patterns indicated that magnesium diboride (MgB2) is a major phase and magnesium oxide (MgO) is the secondary phase. However, no unreacted Mg was detected by XRD at all annealing temperatures. The SEM images showed hexagonal grain structures with nano thickness distributions. The highest critical current density (Jc) at 5 K and 20 K was found in sample annealed at 700 °C. At 5 K and 6 T, the highest Jc achieved was 1.2×104 A/cm2 . At 20 K, the highest Jc achieved by 3.6×103 A/cm2 . The values of the onset superconducting transition temperature, Tc for all Mg0.8B2 were 37.0 K. The samples annealed at 700° C showed a sharper diamagnetic drop with ∆Tc = 3.0 K compared to all samples.